Donor Dopamine Does Not Affect Liver Graft Survival: Evidence of Safety From a Randomized Controlled Trial. Issue 10 (25th October 2018) - Benck, Urs; Jung, Matthias; Krüger, Bernd; Grimm, Anja; Weiss, Christel; Yard, Benito A.; Lehner, Frank; Kiessling, Anja; Fischer, Lutz; Gallinat, Anja; Kleespies, Axel; Lorf, Thomas; et al.
Abstract : Treatment of donation after brain death (DBD) donors with low‐dose dopamine improves the outcomes after kidney and heart transplantation. This study investigates the course of liver allografts from multiorgan donors enrolled in the randomized dopamine trial between 2004 and 2007 (clinicaltrials.gov identifier: NCT00115115). There were 264 hemodynamically stable DBDs who were randomly assigned to receive low‐dose dopamine. Dopamine was infused at 4 μg/kg/minute for a median duration of 6.0 hours (interquartile range, 4.4‐7.5 hours). We assessed the outcomes of 212 liver transplantations (LTs) performed at 32 European centers. Donors and recipients of both groups were very similar in baseline characteristics. Pretransplant laboratory Model for End‐Stage Liver Disease score was not different in recipients of a dopamine‐treated versus untreated graft (18 ± 8 versus 20 ± 8; P = 0.12). Mean cold ischemia time was 10.6 ± 2.9 versus 10.1 ± 2.8 hours ( P = 0.24). No differences occurred in biopsy‐proven rejection episodes (14.4% versus 15.7%; P = 0.85), requirement of hemofiltration (27.9% versus 31.5%; P = 0.65), the need for early retransplantation (5.8% versus 6.5%; P > 0.99), the incidence of primary nonfunction (7.7% versus 8.3%; P > 0.99), and in‐hospital mortality (15.4% versus 14.8%; P > 0.99). Graft survival was 71.2% versus 73.2% and 59.6% versus 62.0% at 2 and 3 years (log‐rank P = 0.71). Patient survival was 76.0% versus 78.7% and 65.4% versus 69.4% at 1 and 3 years (log‐rank P = 0.50). In conclusion, donor pretreatment with dopamine has no short‐term or longterm effects on outcome after LT. Therefore, low‐dose dopamine pretreatment can safely be implemented as the standard of care in hemodynamically stable DBDs.